Grave birds : a novel - Elmendorf, Dana (Mira, 2025)
"Hollis Sutherland has an uncanny gift that allows her to see grave birds, manifestations of the dead's unfinished business; and when a mysterious bachelor wanders into her small town, bizarre events begin to plague its wealthiest citizens and Hollis must work against these evil forces to save the town and herself."--